Perlindungan Konsumen terhadap Kerugian Kesehatan Akibat Keracunan Makanan Bakso Bakar Ditinjau dari Undang-Undang Nomor 8 Tahun 1999 tentang Perlindungan Konsumen - Nanda Eka Prasetya; Arief Rachman Hakim (Jurnal Hukum Lex Generalis, 2025)
The research examines consumer protection due to losses from grilled meatball poisoning in terms of Law Number 8 of 1999 concerning Consumer Protection. The legal problem was caused by consumers experiencing health losses due to poisoning caused by grilled meatballs in Padang City. The aim of the research is to examine the protection and resolution of consumer losses due to grilled meatball poisoning. The method used is a literature study with data collection through document review appropriate for normative legal research. The approaches applied include a statutory approach, a conceptual approach, and a case study approach. The research is expected to provide knowledge of protection and legal certainty for consumers if losses occur due to negligence or deliberate intent of producers in the business field.